Compatibility Of Students' Workbook For Second Year Student Of Sma In Surakarta And Basic Competencies Of Schools' Curriculum Academic Year 2010/2011 - Yuliani, Yuliani (2012)
This study is aimed at examine the compatibility of students' workbook for second year student of SMA in Surakarta and basic competencies of schools' curriculum academic year 2010/2011. The result of the study is expected to contribute to evaluate the compatibility of basic competence of the students' workbook and basic competence of school curriculum academic year 2010/2011. The study was conducted by evaluate the compatibility of the material of the student' workbook with the basic competence of content standard issued by Institution for National Standard of Education (BSNP). The researcher took 2 students' workbook. The book is used by second year students of Senior High School on the first and second semester. The object of the research was the evaluation of the compatibility between basic competence of standard competence in school-based curriculum and basic competence of the students' workbook. The researcher gets the data of this research from the document. The techniques of collecting data are observation and documentation. The result of the study shows that Students' workbook is used by second year student of SMA in Surakarta is very good. It can be used to improve students' English skill and help the students to develop their English knowledge. It means that the teacher and educator knew the quality of any workbook. They choose appropriate supplementary material to help them gain the aims of national education.